An All‐Organic Self‐Powered Photodetector with Ultraflexible Dual‐Polarity Output for Biosignal Detection. Issue 30 (22nd June 2022) - Yan, Tingting; Li, Ziqing; Cao, Fa; Chen, Jiaxin; Wu, Limin; Fang, Xiaosheng
Abstract: Endowing photodetectors with mechanically flexibility and actual functionality are current research issues in developing optoelectronic devices. However, rigid metal‐based or metal‐oxide‐based electrodes remain a block to the realization of ultraflexible electronics. Thus, an ultraflexible all‐organic photodetector (all‐OPD) is designed by innovatively introducing symmetrical organic electrodes PH1000/PH1000 to substitute the widely applied indium‐doped tin oxide (ITO)/Ag electrodes. Specifically, this all‐OPD exhibits a high self‐powered responsivity ( R ) of over 100 mA W −1 among 500–600 nm and the photocurrent remains about 80% of the original performance after being bent 20 000 circles, and can output steady biosignals for photo‐plethysmography (PPG) application. More importantly, this all‐OPD outputs dual‐polarity photocurrent as it is flipped or folded. Benefitting from the ordered phase distribution and designed Schottky barrier heights, the photogenerated holes will be transferred and collected by nearer electrode, while electrons will be trapped in the thick bulk heterojunction (BHJ) as a result of the long channel. This work offers a new avenue toward developing a multifunctional and ultraflexible all‐OPD with a straightforward all‐solution method, and it is expected to be more compatible in complex application scenarios. Abstract : An all‐organic self‐powered photodetector with ultraflexibility and dual‐polarity output is successfully fabricated by an all‐solution method, which is expected to have great application potential in realizing multifunctional, portable, and wearable electronic devices.